PROBLEMATIK YURIDIS PEMBUKTIAN TINDAK PIDANA KORUPSI DENGAN MENGGUNAKAN AUDIT KEUANGAN BPK DAN BPKP - Bernatd Jufly; Erdianto '; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Corruption is no longer a crime that can be classified as a conventional crime. As a crime of extraordinary crime, when viewed from the victim, what is generated from this crime is not limited to individuals but the community, nation and state. So this crime has caused a setback for Indonesia. One element of the corruption offense is the "State Financial Loss", in Article 6 letter a of Law Number 30 of 2002 concerning the Corruption Eradication Commission, it states that "the Corruption Eradication Commission can coordinate with agencies authorized to eradicate corruption". One of the problems that occur regarding supervision of state finances is which state institution has the right to determine the existence of a state loss. Particularly between the BPK and BPKP because of the differences in the results of calculating State losses carried out by the BPK and BPKP at the local government level. This lack of clarity causes a problem for law enforcement officials to use the audit results from the BPK or BPKP. This study uses a normative legal research typology or what is also called doctrinal legal research which more specifically discusses the principles of law. In this study the author uses the meaning of descriptive research, because the author describes the problematic juridical proof of criminal acts of corruption by using BPK and BPKP financial audits. The results of the research conducted by the authors are that there are contradictions between the two institutions that clearly have different positions, roles and authorities, and legislation needs to be clearly and logically established and ideal in regulating state financial audits related to proof of criminal acts of corruption. This is needed so that there will be no multiple interpretations or doubts. Keywords: Problems-Proof of corruption-financial audit